2017
DOI: 10.1016/j.orggeochem.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Long term change in chemical properties of preindustrial charcoal particles aged in forest and agricultural temperate soil

Abstract: Keywords:Preindustrial charcoal kiln Land-use change Biochar X-ray photoelectron spectroscopy (XPS) Differential scanning calorimetry (DSC) Fourier Transform Infrared Spectroscopy (FTIR) 13 C nuclear magnetic resonance ( 13 C NMR) Dichromate oxidation a b s t r a c t Black carbon (BC) plays an important role in terrestrial carbon storage. Nevertheless, the effect of cultivation on long term dynamics of BC in soil has been poorly addressed. To fill this gap, we studied the chemical properties of charcoal partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 61 publications
2
55
0
Order By: Relevance
“…Furthermore, the similar functional groups observed on aged biochar may have been the direct reason for similar pH values. Hardy et al (2017) suggested that carboxylic acids, as well as phenolic acids of aged biochar decreased gradually with cultivation time. It implied that the decreased functional groups might lead to aged biochar pH increase.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…Furthermore, the similar functional groups observed on aged biochar may have been the direct reason for similar pH values. Hardy et al (2017) suggested that carboxylic acids, as well as phenolic acids of aged biochar decreased gradually with cultivation time. It implied that the decreased functional groups might lead to aged biochar pH increase.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…Examples of change would be exposure to oxidation via excavation (Marin-Spiotta et al, 2014), and changes in soil pH via climatic changes or alteration in land-use practice (c.f. Hardy et al, 2017). Although ancient PyC does not necessarily contain ever-increasing levels of SPAC as a precondition for its preservation, chemical degradability (at least in laboratory conditions) does appear strongly linked to the amount of SPAC in the sample, in an inverse proportional relationship (Ascough et al, 2010a(Ascough et al, , 2011a.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the infill does not penetrate throughout the entirety of the samples as the SEM and XRF analyses were on different regions of each PyC sample. We also note that this does not preclude the deposition/precipitation of Ca-rich minerals on internal pores or surfaces on a scale that may only be visible at higher magnification, or at the molecular level via the strong affinity of Ca2+ to carboxylic groups (Hardy et al, 2017). Specimen NNB ( Figure 5D) shows wood in tangential longitudinal section with mainly uniseriate rays and one biseriate ray near base left of image.…”
Section: Scanning Electron Microscopy and Energy Dispersive X-ray Spementioning
confidence: 96%
“…This pretreatment aimed to deprotonate most carboxylic acids present at the surface of charcoal, and to saturate carboxylate anions with Ca 2+ . Hardy et al (2017b) showed that the presence of Ca decreases the thermal stability of the O-rich fraction of charcoal. This then prevents peaks from overlapping, which would otherwise bias the quantification of BC content.…”
Section: Quantification Of Charcoal-c Contentmentioning
confidence: 99%